Students' Problem-Solving Skills on Heat Concepts: A Rasch-Based Analysis Using Classroom Assessment - Adhelia Tasya Youlanda; Mukhayyarotin Niswati Rodliyatul Jauhariyah (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
This study aimed to analyze students’ problem-solving skill profiles on the topic of heat using a Classroom Assessment instrument. A quantitative descriptive method was applied to 107 eleventh-grade students at SMA Negeri 8 Surabaya. Data were collected through a problem-solving test, worksheet assessment, science process skills observation, attitude observation, and attitude questionnaire. Rasch Model analysis using Wright Map and Person Measure was employed. Results showed that in the cognitive domain, 5 students were categorized as high, 58 as medium, and 44 as low. In the science process domain, observations classified 34 students as high, 23 as medium, and 50 as low, while worksheet assessments showed 42 high, 42 medium, and 23 low. In the attitude domain, observations resulted in 22 high, 51 medium, and 34 low, whereas questionnaires showed 16 high, 82 medium, and 9 low. Overall, students’ problem-solving skills were predominantly in the moderate category across cognitive, skills, and attitude domains. These findings indicate that students generally performed well on basic tasks but still require support in higher-order thinking, complex reasoning, and advanced science process skills.